Guide to Computer Forensics and Investigations - Nelson, Bill; Phillips, Amelia; Steuart, Chris (Mason, OH : Cengage Learning US, 2019)
Providing authoritative information, powerful instructor resources and real-world student applications, Nelson/Phillips/Steuart's GUIDE TO COMPUTER FORENSICS AND INVESTIGATIONS, Sixth Edition delivers the most comprehensive forensics resource available. This proven author team's wide-ranging areas of expertise mirror the breadth of coverage in the text, which focuses on techniques and practices for gathering and analyzing evidence used to solve crimes involving computers and other digital devices. Providing clear instruction on the tools and techniques of the trade, it introduces readers to every step of the computer forensics investigation--from lab setup to testifying in court. It also details how to use current forensics software and provides free demo downloads of popular tools like FTK Imager for use with Case Projects and Hands-On Projects. MindTap Computing is also available.
Cover; Brief Contents; Table of Contents; Preface; Introduction; Chapter 1: Understanding the Digital Forensics Profession and Investigations; An Overview of Digital Forensics; Preparing for Digital Investigations; Maintaining Professional Conduct; Preparing a Digital Forensics Investigation; Procedures for Private-Sector High-Tech Investigations; Understanding Data Recovery Workstations and Software; Conducting an Investigation; Chapter Summary; Key Terms; Review Questions; Hands-On Projects; Case Projects; Chapter 2: The Investigator's Office and Laboratory.
Keywords: Computer crimes -- Investigation; Computer security